2014
DOI: 10.1155/2014/602647
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Digital Camera to Monitor the Growth and Nitrogen Status of Cotton

Abstract: The main objective of this study was to develop a nondestructive method for monitoring cotton growth and N status using a digital camera. Digital images were taken of the cotton canopies between emergence and full bloom. The green and red values were extracted from the digital images and then used to calculate canopy cover. The values of canopy cover were closely correlated with the normalized difference vegetation index and the ratio vegetation index and were measured using a GreenSeeker handheld sensor. Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…Compared with other image parameters, CC is obtained more easily and is not affected by weather or light intensity. The R 2 value of the model to predict PNA was 0.6768 (RMSE, 11.6925 g.m -2 ), lower than that reported for cotton [18]. This is because rice, as a dryland crop, has a more complex growing environment than that of cotton, and image processing is affected by complex environmental factors such as water.…”
Section: Comparison Of Methods To Estimate Rice N Statusmentioning
confidence: 65%
See 2 more Smart Citations
“…Compared with other image parameters, CC is obtained more easily and is not affected by weather or light intensity. The R 2 value of the model to predict PNA was 0.6768 (RMSE, 11.6925 g.m -2 ), lower than that reported for cotton [18]. This is because rice, as a dryland crop, has a more complex growing environment than that of cotton, and image processing is affected by complex environmental factors such as water.…”
Section: Comparison Of Methods To Estimate Rice N Statusmentioning
confidence: 65%
“…constructed a regression model of a maize N nutrition index using a dual-band spectral index (R710, R512) [24], and it was proven to be a can describe plant color [25], which can reflect its nutrient status, especially N content and absorption. Several studies have shown that RGB color space parameters extracted from vegetation canopy images can be used to predict vegetation yield and nutrient status [14,18,19]. Among the models constructed with image parameters, those constructed using NRI and GMR were unstable, possibly because the parameters of NRI and GMR were obtained by extracting RGB values from images.…”
Section: Comparison Of Methods To Estimate Rice N Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-ground remote sensing is becoming increasingly important in modern agriculture production (Jia et al, 2014). Ground-based observations of crop growth provide fast, real-time, non-destructive, automatic, and relatively inexpensive information about crop status (Jia et al, 2014).…”
Section: Digital Analysismentioning
confidence: 99%
“…Near-ground remote sensing is becoming increasingly important in modern agriculture production (Jia et al, 2014). Ground-based observations of crop growth provide fast, real-time, non-destructive, automatic, and relatively inexpensive information about crop status (Jia et al, 2014). This information can significantly increase yields by allowing growers to properly time cultivation, fertilizer application, irrigation, pest control, and harvest (Jia et al, 2014).…”
Section: Digital Analysismentioning
confidence: 99%